Relationships between Brands and Customers in a World of Social Networks - Pereira, H.; Salgueiro, M.F.; Mateus, I. (International Network of Business and Management Journals – INBAM, 2013)
The purpose of this paper is to investigate the role of Facebook for the establishment of relationships between brands and its fans, and fits in an extension of the link between Relationship Marketing and Online Consumer Behavior. The paper explores what drives a user to connect to a brand profile on Facebook, to participate and interact with the community, as well as to share contents published by brands on their profiles. To understand this relationship, a methodology combining qualitative and quantitative research techniques was adopted. The qualitative study was based on in-depth interviews to online marketing specialists and on a focus group with Facebook users that were brand followers in this social network. The quantitative study was based on a structured questionnaire, which gathered 650 Facebook brand followers. The proposed theoretical model was tested using structural equation modeling. The results show that Facebook users are willing to connect to brands on Facebook. Despite this willingness, users do not seem to interact or frequently share contents published by brands. As a consequence, brands must face new challenges in order to establish a relationship with their brand profile fans.